Correlation between tax holidays and earning management: An empirical study (Kolerasi antara percutian cukai dengan pengurusan perolehan : satu analisis empirikal) - Zinatul Ashiqin Bachek; Norsiah Ahmad; Norman Mohd Saleh (Penerbit Universiti Kebangsaan Malaysia, 2012)
This study investigates tax avoidance activities among tax-exempt malaysian companies.Pioneer status companies to manage earnings by shifting income throught certain periods and thereby minimizing tax liabilities. Following the literature, discretionary current accruals are used as proxy for earnings management. A control sample is introduced to identify abnormal accruals induced by the pioneer status of companies.Multiple regression analysis indicates that companies manage their earnings to minimize their taxburden. Specifically, pioneer status companies in Malaysia accelerate revenues to the year prior to the expiration of their tax exemptions to reduce tax liabilities in subsequent years.